A FRACTIONAL-ORDER MATHEMATICAL MODEL OF THE SPREAD OF INFLUENZA - Akbar, Abyan Daffa; Fatmawati, Fatmawati; Ahmadin, Ahmadin (PATTIMURA UNIVERSITY, 2025)
Influenza is an infectious disease that has become a public health concern and affects millions of people every year. In Indonesia, 1,527 people were recorded as being infected with influenza from May 2013 to April 2016. In this article, a fractional-order mathematical model of influenza spread was formulated in the sense of Caputo derivative. Based on the model analysis, we obtained two equilibrium points: the disease-free and endemic equilibria. The disease-free equilibrium point is locally asymptotically stable if the basic reproduction number is less than one. Meanwhile, the endemic equilibrium point exists and tends to be asymptotically stable whenever the basic reproduction number is greater than one. Next, a sensitivity analysis was carried out to determine whether changes in parameter values affect the increase or decrease in the value of the basic reproduction number. Lastly, the numerical simulation of the fractional-order model is demonstrated to support the analytical results.